Establishment of an animal model of vascular dementia - WANG, HAO (D.A. Spandidos, 2014)
The aim of this study was to establish a mouse model of vascular dementia (VaD) in order to overcome the shortcomings of rat models of VaD, which include high production costs, difficult surgery, surgical trauma and high mortality. In this study, repeated ischemia-reperfusion of the total bilateral carotid artery in mice, combined with a reduction of blood pressure, was used to establish an animal model of VaD. A total of 40 Kunming mice (clean grade) were randomly divided into a sham group and a model group. Behavioral tests were performed for each group following the surgery, and the morphology of the hippocampus was analyzed. The results of the step-down avoidance test, water maze test and microscopy examinations confirmed that following surgery, learning and memory dysfunction was significantly increased in the model group. The results of the morphological observations showed that the number of hippocampal CA1 neurons was significantly decreased in the model group compared with that in the sham surgery group (P<0.01). In the present study, a mouse model of VaD was successfully established, which was simple, effective and reliable, and may be used in the future to investigate VaD.